Peran Serta Kontribusi Pondok Pesantren Dalam Catatan Sejarah Bangsa Indonesia - Rooby Pangestu Mulyo (LPPM UIN Saizu Purwokerto, 2022)
This article seeks to explore the role and contribution of Islamic boarding schools from the beginning of their emergence in Indonesia. Basically, islamic boarding schools are Islamic educational institutions that have a different pattern from general educational institutions. Islamic boarding schools try to educate their students with various existing knowledge, both general science and Islamic religion. In addition, islamic boarding schools educate their students to have good adab and try to have a good impact on the presence of islamic boarding schools in the scope of community life. And it is proven that islamic boarding schools have a role and contribute to the history of the Indonesian nation.